بروتوكول مصادقة قياسي جديد EPS2-AKA - Ahmad, Ahmad Saker; State, Amane (Latakia University Journal -Engineering Sciences Series, 2019)
بروتوكول مصادقة قياسي جديد EPS2-AKA أحمد صقر أحمد أماني ستيتي تُعد الشبكات المتطورة طويلة الأمد (LTE)Long Term Evolution أحدث تقنيات الشبكات الخلوية، والتي توفر خدمات عالية السرعة للأجهزة المحمولة، نطاق أكبر ، كفاءة طيف أفضل، تغطية أوسع وبنية أمنية متطورة. فقد اقترح مشروع شراكة الجيل الثالث 3GPP(Third Generation Partner Project) بروتوكول المصادقة نظام الحزم المتطور واتفاق المفتاح EPS-AKA(Evolved Packet System Authentication Key Agreement) لتحقيق المتطلبات الأمنية لنظام الحزم المتطور في شبكات LTE ، ولكن هذا البروتوكول لايزال لديه بعض العوائق في عملية المصادقة بسبب نقاط الضعف الموروثة من البروتوكولات السابقة. نقترح في هذا البحث البروتوكول EPS2-AKA تطويراً لبروتوكول نظام الحزم المتطور EPS-AKA لتعزيز مستوى الأمن، وتغطية نقاط الضعف دون تكلفة إضافية عن طريق إخفاء كامل للمعرٌف IMSI(International Mobile Subscriber Identity) مع اختبار للبروتوكول المقترح باستخدام الأدة SPAN (Security Protocol ANimator for AVISPA) للتحقق من مستواه الأمني، ومقارنته مع البروتوكول القياسي EPS-AKA من حيث الحمل على الشبكة. Long Term Evolution (LTE) networks are the latest cellular network technologies that provide high-speed mobile services, greater range, better spectrum efficiency, wider coverage and improved security architecture. 3GPP (Third Generation Partner Project) has proposed the Advanced Evolved Packet System Authentication Key Agreement (EPS) to meet the security requirements of the advanced LTE packet system, but this protocol still has some drawbacks in the process Authentication because of vulnerabilities inherited from previous protocols. In this research, we propose the EPS2-AKA protocol development of the advanced EPS-AKA protocol system to enhance the security level and cover the vulnerabilities at no additional cost by fully hiding the International Mobile Subscriber Identity (IMSI) and testing the proposed protocol using the SPAN (Security Protocol ANIMATOR for AVISPA) Its security level, and compare it with the standard EPS-AKA protocol in terms of load on the network.